1990
DOI: 10.1016/0014-5793(90)81419-o
|View full text |Cite
|
Sign up to set email alerts
|

Diverse actions of cadmium on the smooth muscle myosin phosphorylation system

Abstract: The effects of cadmium (Cd) on smooth muscle myosin phosphorylation have been investigated using an in vitro system comprising myosin filaments containing endogenous calmodulin (CM) and myosin light chain kinase (MLCKase), In the absence of calcium (Ca), Cd as well as some other divalent cations caused no activation ofphosphorylation. However, when at least one (or possibly two) Ca 2 + were bound per CM, the addition of 10/~M to 40/tM Cd 2+ resulted in a 2 to 3 fold acceleration of the phosphorylation rate. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The possibility still exists, however, that Cd interferes with the downstream cascade of cAMP-protein kinase A-dependent pathway. Kostrzewska and Sobieszek [45] reported that higher Cd concentrations inhibited the phosphorylation of myosin light-chain kinase in the smooth muscle myosin, suggesting that Cd interferes with the phosphorylation of protein kinases. An additional possibility is that the metal may directly affect transcription of P450 scc by interfering with the DNA binding zinc finger motif through the substitution of Cd 2ϩ for Zn 2ϩ [46].…”
Section: Discussionmentioning
confidence: 98%
“…The possibility still exists, however, that Cd interferes with the downstream cascade of cAMP-protein kinase A-dependent pathway. Kostrzewska and Sobieszek [45] reported that higher Cd concentrations inhibited the phosphorylation of myosin light-chain kinase in the smooth muscle myosin, suggesting that Cd interferes with the phosphorylation of protein kinases. An additional possibility is that the metal may directly affect transcription of P450 scc by interfering with the DNA binding zinc finger motif through the substitution of Cd 2ϩ for Zn 2ϩ [46].…”
Section: Discussionmentioning
confidence: 98%
“…Although Cd 2+ is best known as a Ca 2+ channel blocker, it can also activate calmodulin and have other effects as well (e.g., Kostrzewska and Sobieszek, 1990;Behra, 1993). …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in the absence of calcium, high concentrations of cadmium binds to adenosine triphosphate and does not affect smooth muscle phosphorylation [42].…”
Section: Discussionmentioning
confidence: 99%